AKTIVITAS EKSTRAK RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb.) SEBAGAI LARVASIDA TERHADAP Aedes aegypti DI KECAMATAN KELAPA LIMA KOTA KUPANG - Deswandi W. S. Berri; Julianty Almet; Diana Agustiani Wuri (JURNAL KAJIAN VETERINER, 2020)
Dengue hemorrhagic fever (DHF) is a disease that is found in some tropical and subtropical regions. This disease is caused by dengue virus and is transmitted to humans through the bite of the Aedes aegypti mosquito. the solution taken in controlling DHF is to break the life cycle of the Aedes aegypti mosquito. Vector control is generally carried out using synthetic larvicides, namely abate / temefos, but the use of abate can cause residues, environmental pollution, poisoning and resistance of the eradicated vectors so that natural larvasides from plants are needed namely temulawak rhizome (Curcuma xanthorrhiza Roxb.) for vector control. The purpose of this study was to determine whether temulawak rhizome extract was effective or not in killing Aedes aegypti larvae. This research method includes larva collection, identification and maintenance of mosquitoes, determining sample size, making extracts and testing effectiveness. This study used a control and experiment group with 3 repetitions in the minutes to 15, 30, 45, 60 and 1440 (24 Hours). The control group was positive control using abate and negative control using aquades while the eksperiment group used extract of temulawak rhizome (Curcuma xanthorrhiza Roxb.) with concentrations of 0.6%, 0.8%, 1%, 1.2% and 1.5%. The results of this study indicate that the temulawak rhizome extract (Curcuma xanthorrhiza Roxb.) effective as larvicides because at the lowest concentration 0.6% can kill 100% Aedes aegypti larvae.